IMPACT OF BLOCKING SOME MAJOR SENSORY INPUTS ON THE FEEDING BEHAVIOUR OF PERIPLANETA AMERICANA (BLATTARIA : BLATTIDAE) - SMITH, V. ROBIN PERINBA; RAJKUMAR, R.; DAS, SAM MANOHAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
The time taken by control Periplaneta americana adults kept confined in a chamber, to track down food placed at the food rack in the chamber was noted. The food tacking time increased significantly when the animals were antenectomized or eye blocked in various combinations. The co-ordination of the eyes and antennae in sensory input has been discussed.